Assessing Psychomotor Domain in Civil Engineering Design Project During Pandemic / Fei Ha Chiew ... [et al.] - Bidaun, Beatrice Christianus; Joseph Sipi, Rudy Tawie (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Previous studies highlighted the challenges in assessing psychomotor skills in engineering education when using online platforms. The main aim of this study was to examine the effectiveness of learning psychomotor skills online in Civil Engineering Design Project during the pandemic. This paper discusses the challenges faced in assessing the psychomotor domain in Civil Engineering Design Project during the pandemic and the immediate actions taken during the semester. New structural engineering software was used as the initial software was not accessible outside campus. The greatest challenge for lecturers was to learn the new software within a short period and to implement the use of the new software in their teaching and learning activities as well as in the students' assessments. New evaluation rubrics were created to assess students' psychomotor skills in using the new software for course assessments. Marks were allocated to each practical skill identified in completing the assessments. Students' grade attainments of the two course outcomes mapped to the psychomotor domain show that more than 85% of students were able to achieve the KPI of 50% for the two course outcomes. This shows that most students were able to grasp the relevant practical skills required in the course when taught via ODL.